PREDIKSI FINANCIAL DISTRESS DARI PERSPEKTIF FINANCIAL INDICATORS DAN OWNERSHIP STRUCTURE - Putu Diah Pratiwi; Luh Komang Merawati; Daniel Raditya Tandio (Journal Research of Accounting, 2023)
The purpose of this study is to determine the relationship between financial indicators and ownership structure in predicting financial distress. Indicators of financial used in this study include sales growth, ROA-measured profitability, and DAR-measured leverage, while institutional and managerial ownership are shown by the ownership structure. The population are manufacturing companies listed on the Indonesia Stock Exchange in 2019-2021 with 78 sample obtained using purposive. This study used logistic regression as a data analysis tool. The results shown that ROA has a negative effect on financial distress prediction. Sales growth has a positive effect on financial distress prediction. Whille leverage, managerial and institutional ownership did not affect on financial distress prediction in manufacturing companies.